Analysis of Determination Factors on Human Resources Development and Performance of Employees, Culture, Youth and Sports of Gorontalo - Andi Yusniar Mendo (AIBPM Publisher, 2018)
The research aims: 1) analyzed the effect of leadership and organization commitment as the determinant factor and development of human resource toward performance by employee; 2) analyzed the determinant factor such as leadership and organization commintment toward development of human resource; and 3) analyzed the both of determinant factor namely the leadership toward organization commitment. The location of research in Gorontalo City, in Instance of Education, Culture, Youth and Sport. Population and sample as amount 171 responden (full sampling). Data from questioner to analyzed with path analysis. The result of research to found: 1) the ladership have positive and insignificant toward performance of employee. The applied of leadership to actualization, unless insiginificant toward increased the performancey by employee; 2) the organization commitment have postive and significant toward performance by employee. The organization commitment have actualize suitable with the work routine in increasing of performance by employee; 3) the development of human resource have postive and significant toward performance by employee. The development of human resource is important in attempt of increased the performance by employee; 4) the leadership have postive and significant toward development of human resource. The leadership able to directed, moved and effected of the potency by employee in working; 5) the organization commitment have postive and significant toward development of human resource. The organization commitment to development of carreer oriented to inovation and technology which effected of development by human resource: 6) the leadership have postive and significant toward organization commitment. The leadership which applied able to increased the commitment of organization in working. Keywords: Leadership, Organization Commitment, Development of Human Resource and Performance by Employee